Prohibition of Abuse of Rights in Serbian Law: A Legal-Historical Analysis of the Norm in the Period Between Two Civil Codes - Boranijašević, Vladimir D.; Radulović, Srđan M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
In order for legal entities to realize their material or non-material interests, the legal order grants them a set of subjective rights and individual entitlements. The exercise of these rights directly affirms the legal order, while the pursuit of individual interests indirectly contributes to the realization of its objectives to which the legal order aspires. This is the general rule. However, in certain situations, the exercise of rights may amount to a negation of the legal order. Although this may seem counterintuitive, the conduct of a subject can be qualitatively equated with unlawful behaviour, even when the individual formally remains within the boundaries of their entitlements. This occurs when a person, in exercising a right, compromises the legal interests of others to an unacceptable extent, and especially when the right is exercised without any legitimate interest but solely to cause harm. In such circumstances, it is not accurate to say that the person is merely exercising a right; rather, they are abusing it. Nor can such conduct be considered permissible; on the contrary, it is impermissible. Such conduct undermines the legal order. Therefore, it is first necessary to identify it correctly, that is, to establish criteria by which permissible and impermissible exercises of rights can be reliably distinguished. Second, it is necessary to develop an adequate system of sanctions to be applied once those criteria are met. The prohibition of the abuse of subjective rights serves as one of the foundations for correcting the behaviour of legal subjects. The history of abusive exercise of rights in domestic legal theory is exceptionally long. However, when we speak of the abuse of rights as a legally and technically structured, codified institution, its history in our law can be traced back to the enactment of the Serbian Civil Code. The Republic of Serbia has initiated the process of drafting a new Civil Code. As things stand, it is almost certain that the prohibition of the abuse of rights will be an integral part of it. Therefore, a correct understanding of a norm whose evolution has spanned nearly two centuries is of great scientific, social, and practical significance. This paper presents the results of a theoretical-empirical study that identified the salient phases in the development of this institution. The research was conducted primarily using the normative method, in its historical, positive, and, to some extent, comparative-legal variants. The results are presented chronologically, following the dynamics of amendments and supplements to relevant regulations.